PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN BOLAANG MONGONDOW TIMUR - Jelita Lapadjawa; Olfie L.S. Benu; Grace A.J. Rumagit; Welson M. Wangke (COCOS, 2014)
ABSTRACTJelita Lapadjawa, 100314045, Role of the Agricultural Sector of the Economy East Bolaang Mongondow Regency under the guidance of Olfie L.S Benu as chairman, Grace A. J Rumagit and Welson M. Wangke as members. This study aims to determine (1) the role of the agricultural sector in the East Bolaang Mongondow Regency Economy, (2) the development of the agricultural sector within 5 years, from 2008 to 2012, and (3) whether the agricultural sector is a base or non base sector. The research was conducted in the East Bolaang Mongondow Regency. The data used was secondary data, collected from Statistics Indonesia (BPS) both at Kotamobagu City Office and North Sulawesi Province Office. The data was then analyzed using the contribution formula, the growth formula, and Location Quotient (LQ).The results showed that the agricultural sector was not the biggest contributor to the regional economy of the East Bolaang Mongondow Regency. The results of the study alsonoted that the development of the agricultural sector to the GRDP showed an increase from the year 2008- 2012, with the largest increase occurred in 2010 with the growth rate of 6%, and in 2012 it reached 4.66%. This could mean that the agricultural sector in the East Bolaang Mongondow already had good productivity. From the LQ analysis, it was shown that Agriculture was a base sector in the East Bolaang Mongondow, meaning that the role of agriculture in the East Bolaang Mongondow was larger compared its role in the province of North Sulawesi. Moreover, within Agriculture sector, it was shown that forestry, plantations and farms were the leading subsectors.